Effect of low concentration Sn doping on optical properties of CdS films grown by CBD technique - Jafari, Atefeh; Zakaria, Azmi; Rizwan, Zahid; Mohd Ghazali, Mohd Sabri (MDPI, 2011)
Thin and transparent films of doped cadmium sulfide (CdS) were obtained on commercial glass substrates by Chemical Bath Deposition (CBD) technique. The films were doped with low concentration of Sn, and annealed in air at 300 °C for 45 min. The morphological characterization of the films with different amounts of dopant was made using SEM and EDAX analysis. Optical properties of the films were evaluated by measuring transmittance using the UV-vis spectrophotometer. A comparison of the results revealed that lower concentration of Sn doping improves transmittance of CdS films and makes them suitable for application as window layer of CdTe/CIGS solar cells.